Studying of full-duplex transmission in 5G communications - Dhanraj, Hariharan (2019)
This report mainly involves the study of full-duplex (FD) transmission in the fifth-generation (5G) communication. The detailed study of the implementation of FD in 5G is elaborated. FD transmission is a well-known technique to double the spectral efficiency in wireless communications. However, this technique is hindered by self-interference. Recent research reveals that self-interference can be completely eliminated, which enables FD transmission on transceivers with high spectral efficiency for small-cell base stations. Accordingly, FD transmission is regarded as a strong candidate enabling 5G cellular networks. In this project, the FD technology is investigated in various environments and an effective application relating to it is also discussed. Inclusive of FD, the remaining types of communication channels are also discussed in detail. Moreover, the list of mobile phone generation along with its evolution is described with practical examples. Furthermore, advanced mitigation techniques are also studied. It is aimed to determine a feasible detection of a scheme that eliminates the loopback-interference caused within the antenna circuit. The performance parameters are explained theoretically for these advanced mitigation techniques and used for future analysis. Each method is deeply discussed with all the possible drawbacks and advantages to short list an ideal technique which eliminates the occurred interference signal circulating within the transmitter antenna